(untitled) (Bangladesh Journal of Agriculture, 2022)
Ectoparasite infestations have direct and indirect negative impacts on its host. Ectoparasite fauna of pigs of Bangladesh is not well documented. Our objective was to detect the ectoparasite fauna among the pigs in Rangamati district of Bangladesh. We examined, 480 pigs from 104 households by close inspection and detected one species of louse (e.g., Haematopinus suis), three species of ticks (Amblyoma testudinarium, Haemaphysalis bispinosa, and Rhipicephalus sanguineus), and one species of flea (Ctenocephalides canis). Pathology and economic losses due to the detected ectoparasites in Rangamati district need further investigation for the betterment of the local pig industry. Bangladesh J. Agri. 2022, 47(1): 88-94